2005
DOI: 10.1111/j.1365-2362.2005.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

22‐ene‐25‐oxa‐vitamin D: a new vitamin D analogue with profound immunosuppressive capacities

Abstract: ZK156979 is a member of novel vitamin D analogues revealing prominent immunomodulatory and suppressive characteristics with distinctive inhibition of Th1-cytokines whereas the Th2 compartment is augmented, thus providing a considerable therapeutic potential in T-cell -mediated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…These data confirm our recent in vitro findings with this analog in phytohemagglutinin-stimulated human PBMCs (Daniel et al, 2005). The substantial amelioration of the clinical parameters of Th1-mediated TNBS-induced colitis was accompanied by a significant down-regulation of the inflammatory response as assessed by MPO activity and local TNF-␣ and IFN-␥ levels.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These data confirm our recent in vitro findings with this analog in phytohemagglutinin-stimulated human PBMCs (Daniel et al, 2005). The substantial amelioration of the clinical parameters of Th1-mediated TNBS-induced colitis was accompanied by a significant down-regulation of the inflammatory response as assessed by MPO activity and local TNF-␣ and IFN-␥ levels.…”
Section: Discussionsupporting
confidence: 80%
“…In a previous in vitro study using human PBMCs, we clearly demonstrated prominent immunosuppressive capabilities for ZK156979, resulting in strong inhibition of the phytohemagglutinin-induced Th1-response (IFN-␥ and TNF-␣), as well as of the macrophage-product IL-1␤ with a molar potency on cytokine expression being only marginally reduced compared with that of calcitriol (Daniel et al, 2005). In addition, in these in vitro experiments ZK156979, in concordance with calcitriol, also affected the Th2 response, leading to significant increases of IL-4 and IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending two previous investigations (Daniel et al, 2005(Daniel et al, , 2006, the data of this in vivo study in an accepted model of Th1-mediated colitis in mice clearly indicates and unravels that combining dexamethasone with calcitriol represents an attractive new immune modulatory treatment regimen of inflammatory disorders, including CD. To our knowledge, here we show for the first time that the complex immunemodulating effects of calcitriol may result from a differential down-regulation of proinflammatory capacities of intestinal DC as assessed by analysis of IL-12p70 as well as IL-23p19.…”
Section: Discussionmentioning
confidence: 95%
“…However, our data should be validated by investigation of a larger study cohort, because of the limited group size. The reports on vitamin D-mediated modulation of T-helper cell polarization in mice and human are heterogeneous (Hayes et al, 2003) and include altered Th1/IFN-g (Daniel et al, 2005), Th2/IL-4 (Hayes et al, 2003), but also tolerogenic responses (Schleithoff et al, 2006;Adorini and Penna, 2008). In this study, we observed a stable recall T-helper cell response on vitamin D regarding the secretion of TT-specific or polyclonally induced IL-2, IL-4, IL-5, IL-10, IFN-g or tumor necrosis factor-a compared with placebo.…”
Section: Discussionmentioning
confidence: 99%